The ABCD database: a repository for chemically defined antibodies. Issue Volume 48:Issue D1(2020) (14th August 2019) - Lima, Wanessa C; Gasteiger, Elisabeth; Marcatili, Paolo; Duek, Paula; Bairoch, Amos; Cosson, Pierre
Abstract: The ABCD (for AntiBodies Chemically Defined) database is a repository of sequenced antibodies, integrating curated information about the antibody and its antigen with cross-links to standardized databases of chemical and protein entities. It is freely available to the academic community, accessible through the ExPASy server (https://web.expasy.org/abcd/ ). The ABCD database aims at helping to improve reproducibility in academic research by providing a unique, unambiguous identifier associated to each antibody sequence. It also allows to determine rapidly if a sequenced antibody is available for a given antigen.